G299 Nusinersen (spinraza) is the first drug approved for spinal muscular atrophy (sma): initial experience in patients with sma type 1 treated in the expanded access program (eap). (12th March 2018) - Scoto, M; Main, M; Munot, P; Edel, L; Abel, F; Chan, E; Manzur, A; Muntoni, F
Abstract : Aim to report the experience in patients with SMA type 1 treated in the Nusinersen expanded access program (EAP) in a single centre that have the largest UK cohort of patients with SMA type 1 (24 patients). Infantile SMA type 1 is the most common form of classic proximal 5q-SMA and also the most severe with inability to achieve independent sitting and limited life expectancy. SMA is caused by mutations in the survival motor neuron 1 ( SMN1 ) gene resulting in insufficient SMN protein levels. Nusinersen (commercial name SPINRAZA) is a modified antisense oligonucleotide that, administered via consecutive intrathecal injections, modulates the splicing of the SMN2 mRNA transcript to include exon 7, thereby increasing the production of full-length SMN protein. Following the promising results of a large international phase II clinical trial (ENDEAR) nusinersen has received FDA and EMA approval and is currently offered under EAP in several European countries. Methods: The motor abilities of all patients recruited in the EAP were systematically assessed using a validated score of motor function developed specifically for patients with SMA type 1 (CHOP-intend scale) and the Hammersmith Infant Neurological Examination-part 2 (HINE-2 motor milestone assessment). Information on SMN2 copies was collected from the patients'' medical records while data on nutrition and respiratory function was collected at each visit prior drug administration. Results: Twenty-one/24 patients with SMA type 1 (age range 3 months-9 years) were recruited into the EAP from March 2017. One patient is under evaluation while two patients are already recruited into an open label trial using the same drug. To date, patients in the EAP tolerated well the lumbar puncture procedure performed using local anaesthetic and no side effects or adverse events related to the drug were noted. In 75% of the patients an improvement of the CHOP-Intend total score was observed after the 4th or 5th injection. Conclusion: Our data confirm the safety of intrathecal Spinraza treatment in SMA type 1 as well as a degree of motor function improvement. More longitudinal data is necessary to evaluate the long-term benefits, the respiratory muscle response and the best responders.